PENERAPAN SISTEM INFORMASI MANAJEMEN DALAM STRATEGI E-COMERCE PENJUALAN HYBIRD DAN MAYA PADA STAR SKINCARE - Vivi Ade Rivani; Hwihanus Hwihanus (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The development of an increasingly sophisticated era creates various kinds of technology. Almost all fields of human work that use information and communication technology that can provide transformation for human life will require a very fast and precise exchange of information. Star Skincare is a skin care sales business located in Surabaya. Currently skin care is something that has a strong appeal in its development in society. In this case the e-commerce strategy has a very influential role in sales rights. The marketing strategy for selling skincare at Star Skincare uses a hybrid sales system and virtual sales. The purpose of this study is to evaluate how the e-commerce sales system at Star Skincare is currently running. Apart from that, it can also help restore the customer's perspective, so that it can create recovery related to the services carried out and can produce customer satisfaction. The method used in this research is qualitative to describe and explain the condition of the topic of study. With the existence of a hybrid and virtual sales system, it can make it easier for people to get information in making transactions.